العامية الجزائريّة وصلتها برواية ورش لهجة منطقة الجلفة وضواحيها أنموذجا - El Djabri Mansouri (Al-Lisaniyyat)
Arabic speakers communicate with each other in the Arab countries in the vernacular, and this language may vary from place to place. It is not hidden from students that connection between colloquial language and classical language and its variations, as well as its connection to Qur'anic readings. Therefore, through this research titled: "Algerian colloquial and its connection to the Warsh narration, the dialect of the Djelfa region and its suburbs as a model," we aim to elucidate the connection of the Djelfa region's dialect with the Warsh narration.